Dukungan Suami, Pengetahuan dan Sikap Pasien Dapat Mempertahankan Motivasi Menjalani Program Kemoterapi - Ace Sudrajat; Dahlia Simajuntak; Nelly Yardes; Eska Riyanti; Dewi Lusiani; Sri Hendra; Sayani Sayani (Jurnal Keperawatan, 2020)
Chemotherapy drugs are proven to be effective in killing cancer cells, but chemotherapy drugs can also cause side effects such as hair loss. These side effects make patients less motivated to undergo chemotherapy programs. The drop-out rate for chemotherapy program patients at the RSCM Polyclinic is 5%. The research objective was to prove the relationship between the knowledge and attitude of the patient and the support of the husband and the patient's motivation to undergo the chemotherapy program. The research method used was cross sectional. Respondents were patients undergoing chemotherapy programs at the RSCM polyclinic. The sampling strategy used was patients who had undergone breast surgery and were actively undergoing chemotherapy. Respondents amounted to 30 people. The results of the bivariate test showed that there was a significant relationship between knowledge and motivation with a value of p = 0.032, attitudes with motivation p = 0.0001, support from husbands with motivation p = 0.0001. Meanwhile, the results of the multivariate test obtained a correlation model where two independent variables (knowledge and family support) had a very strong positive relationship with the patient's motivation to undergo chemotherapy at a significance level of 5% (p = 0.011; R-square model = 0.700). The conclusion is that the better the level of knowledge and attitude of the patient and the full support of the husband, the higher the motivation of the patient to undergo the chemotherapy program. Research recommendations for patients who have dropped out of chemotherapy.